1993
DOI: 10.1007/bf00027178
|View full text |Cite
|
Sign up to set email alerts
|

Screening techniques and sources of resistance to foliar diseases caused by fungi and bacteria in cool season food legumes

Abstract: Screening techniques are an important component of the overall strategy of breeding for resistance to diseases in cool season food legumes . Suitable screening methods have been developed for several major foliar diseases of chickpea, pea, faba bean, and lentil, and sources of resistance have been identified . International cooperation plays an important role in promoting research and keeping collections of cultivated species and their wild relatives . New biotechnological approaches are promising for enhancin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 49 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…Detached leaflet assays have been used to assess reaction of FB varieties against B. fabae (Khalil and Harrison, 1981;Hanounik and Maliha, 1986;Hanounik and Robertson, 1988;Porta-Puglia et al, 1994;Bouhassan et al, 2003Bouhassan et al, , 2004aBouhassan et al, and 2004b. Generally, there was a positive correlation between the detached leaf assays and field evaluations for both susceptible and resistant cultivar, but for moderate resistant cultivars no clear correlation (Bouhassan et al, 2003) has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detached leaflet assays have been used to assess reaction of FB varieties against B. fabae (Khalil and Harrison, 1981;Hanounik and Maliha, 1986;Hanounik and Robertson, 1988;Porta-Puglia et al, 1994;Bouhassan et al, 2003Bouhassan et al, , 2004aBouhassan et al, and 2004b. Generally, there was a positive correlation between the detached leaf assays and field evaluations for both susceptible and resistant cultivar, but for moderate resistant cultivars no clear correlation (Bouhassan et al, 2003) has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The deployment of resistant FB varieties is an efficient strategy for controlling chocolate spot disease and promoting the development of sustainable agriculture (Rhaïem et al, 2002;Bouhassan et al, 2004a). Detached leaflet assays have been widely used for initial screening of large numbers of FB varieties, thereby eliminating highly susceptible accessions before conducting costly field tests (Khalil and Harrison, 1981;Hanounik and Maliha, 1986;Hanounik and Robertson, 1988;Porta-Puglia et al, 1994). These assays also seemed to be useful for identifying the components of partial resistance or evaluating the effect of different factors on the response of FB plants against B. fabae (Bouhassan et al, 2003(Bouhassan et al, ,2004bVillegas-Fernández et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of inoculum and the artificial inoculation procedure were as described by Collard et al (2001), except that plants were sown in seedling trays, placed in plastic containers and covered with transparent polyethylene sheets during inoculation. For the field trial, natural infection was utilized but enhanced by spreader-rows (Porta-Puglia et al 1994) of cultivar Howzat (moderately susceptible). Infected chickpea stubble was also scattered in the field one week after germination to increase infection.…”
Section: Ascochyta Blight Infection Trialsmentioning
confidence: 99%
“…Under such conditions, irrigation after sunset can be effective in maintaining high relative humidity and promoting disease development. Due to the association between plant age and disease susceptibility, Porta-Puglia et al (1994) stated that it is necessary to expose material to the disease at all crop growth stages even after the susceptible check may have been destroyed.…”
Section: Techniques For Screeningmentioning
confidence: 99%